Negative Mood States Are Related to the Characteristics of Facial Expression Drawing: A Cross-Sectional Study - Nanayama Tanaka, Chika; Higa, Hayato; Ogawa, Noriko; Ishido, Minenori; Nakamura, Tomohiro; Nishiwaki, Masato (Frontiers in Psychology, 2020)
An assessment of mood or emotion is important in developing mental health measures, and facial expressions are strongly related to mood or emotion. This study thus aimed to examine the relationship between levels of negative mood and characteristics of mouth parts when moods are drawn as facial expressions on a common platform. A cross-sectional study of Japanese college freshmen was conducted, and 1,068 valid responses were analyzed. The questionnaire survey consisted of participants’ characteristics, the Profile of Mood States (POMS), and a sheet of facial expression drawing (FACED), and the sheet was digitized and analyzed using image-analysis software. Based on the total POMS score as an index of negative mood, the participants were divided into four groups: Low (L), Normal (N), High (H), and Very high (VH). Lengths of drawn lines and between both mouth corners were significantly longer, and circularity and roundness were significantly higher in the L group. With increasing levels of negative mood, significant decreasing trends were observed in these lengths. Convex downward and enclosed figures were significantly predominant in the L group, while convex upward were significantly predominant and a tendency toward predominance of no drawn mouths or line figures was found in the H and VH groups. Our results suggest that mood states can be significantly related to the size and figure characteristics of drawn mouths of FACED on a non-verbal common platform. That is, these findings mean that subjects with low N mood may draw a greater and rounder mouth and figures that may be enclosed and downward convex, while subjects with a high N mood may not draw the line, or if any, may draw the line shorter and upward convex.